Pakistan : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, and Securities Regulation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper evaluates Pakistan's Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, Banking Supervision, and Securities Regulation. Major reforms in the financial sector have resulted in a more resilient and efficient financial system that is better placed to absorb significant macroeconomic shocks. Increased liquidity in the system has recently led to a rapid increase in credit to the private sector that could be problematic if sustained. The securities markets have benefited from recent reforms, but may be vulnerable to systemic risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet